PENGARUH PENGGUNAAN MODEL PICTURE AND PICTURE TERHADAP KETERAMPILAN MENULIS TEKS CERITA FANTASI SISWA KELAS VII SMP NEGERI 7 PARIAMAN - Inayyah Aldrina; Abdurrahman Abdurrahman (Universitas Negeri Padang, 2020)
ABSTRACT The purpose of this study consists of three. First, it describes the writing skills of fantasy text for grade VII Junior High School 7 Pariaman before using the picture and picture models. Secondly, it describes the writing skills of fantasy text of grade VII Junior High School 7 Pariaman using a picture and picture models. Third, describe the effect of using picture and picture models against writing fantasy text skills grade VII Junior High School 7 Pariaman. This type of research is quantitative research with experimental methods. The design of this research is one group pretest-posttest design. The results of this study are three. First, the fantasy text writing skills of grade VII Junior High School 7 Pariaman before using the picture and picture model are in the Almost Enough qualification with an average score of 52.99. Secondly, the skill of writing fantasy text for grade VII Junior High School 7 Pariaman after using the picture and picture model is in the qualification More Than Enough with an average count of 69.53. Third, based on the t-test, the alternative hypothesis (H1) is at a significant level of 95% and the degree of freedom (dk) = n-1 because tcount > t table, which is 4.59 > 1.70. Kata Kunci: pengaruh, model picture and picture, menulis teks cerita fantasi